The Javanese Diaspora in New Caledonia reflected in Ama Bastien’s Le Rêve Accompli de Bandung à Noumea and Marc Bouan’s L’Echarpe et le Kriss - Arifah Arum Candra Hayuningsih (Humaniora, 2022)
New Caledonia is a French Overseas Territorywhose lit erary works do not take the “center stage” in Francophone literature. In particular, the Javanese diasporic community in this archipelago has received relatively little attention from researchers, with past studies largely focusing on Javanese indentured laborers in Suriname, instead. This research examined the autobiographical novels of two New Caledonian writers, Le rêve accompli de Bandung à Nouméa by Ama Bastien and L’écharpe et le kriss by Marc Bouan. These writers belong to the second generation of Javanese immigrants, whose parents came to New Caledonia at the beginning of the 20th century under the indentured laborer scheme. The analysis employed diasporic and cultural identity as its theoretical framework, along with Steven Tötösy de Zepetnek’s comparative cultural studies method. The results explicate the way in which these novels embody the establishment of identity in the Javanese diaspora in New Caledonia. They also demonstrate how the contestation of identity and memory is inextricably linked to the problems of the Javanese diasporic communities. These findings should contribute to and encourage the further study of diasporic communities related to Southeast Asian indentured labor.